2022
DOI: 10.1021/acssuschemeng.1c06048
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Robust Selenium Nanoparticles via Polysaccharide–Polyphenol Interaction: Design Principles and Structure–Bioactivity Relationship

Abstract: Selenium is an essential micronutrient and is well known for its role in regulating metabolism. However, it is also highly toxic in some of its forms and above certain concentration levels. Amorphous selenium nanoparticles (SeNPs) are extremely unstable and convert into non-bioactive or gray elemental selenium with crystal-type structures due to aggregation, which limits its antioxidant and anti-tumor activities. To overcome these limitations, monodisperse SeNPs were obtained by stabilizing SeNPs with glucan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
(89 reference statements)
2
35
0
Order By: Relevance
“…These results suggested the amorphous nature of LNT-SeNPs. Consistent with our results, recent studies reported that the amorphous structure of SeNPs stabilized by glucan or chitosan was observed in the XRD patterns ( 13 , 23 ). The valence state of Se in LNT-SeNPs was analyzed by XPS.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggested the amorphous nature of LNT-SeNPs. Consistent with our results, recent studies reported that the amorphous structure of SeNPs stabilized by glucan or chitosan was observed in the XRD patterns ( 13 , 23 ). The valence state of Se in LNT-SeNPs was analyzed by XPS.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, massive efforts have been taken to stabilize SeNPs through the introduction of templates, which can interact with SeNPs and suppress their aggregation. Besides, using bioactive templates will be helpful for regulating or enhancing the bioactivities of SeNPs ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results were similar to those reported. [ 48,49 ] The above results indicated that SeNPs were successfully prepared.…”
Section: Resultsmentioning
confidence: 80%
“…Previous studies have shown that different methods can induce apoptosis in HepG2 cells. It has been reported that selenium–sorafenib complexes can effectively activate the Ca 2+ signaling system and cause endoplasmic reticulum stress [ 40 ], while glucan-selenium nanoparticles (Glucan-SeNPs) can activate Caspase-3 and Caspase-9 [ 41 ]. This experiment provides a basis for exploring the specific mechanism of apoptosis in the future.…”
Section: Discussionmentioning
confidence: 99%